2022
DOI: 10.1111/bjh.18051
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of infections in patients with acute myeloid leukaemia receiving venetoclax and a hypomethylating agent

Abstract: Summary We investigated the incidence of invasive fungal infections (IFIs) and other infectious complications in patients receiving venetoclax and hypomethylating agent therapy for acute myeloid leukaemia (AML). This retrospective, multicentre cohort study included adult patients with AML who received at least one cycle of venetoclax and either azacitidine or decitabine between January 2016 and August 2020. The primary outcome was the incidence of probable or confirmed IFI. Secondary outcomes included antifung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
5
12
1
Order By: Relevance
“…The rate of proven and probable IFI in our cohort was 5.6%. Our incidence rate was very similar to the 5.1% incidence rate of probable or confirmed IFI from a recent study that also looked at the use of VEN with either AZA or decitabine in patients with AML [ 9 ]. These consistent rates suggest a lower likelihood of IFI incidence than previously reported rates for newly diagnosed AML cohorts that were similarly treated, where the incidence of proven and possible IFIs was 16% for patients treated with hypomethylating agent–based induction therapy [ 12 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The rate of proven and probable IFI in our cohort was 5.6%. Our incidence rate was very similar to the 5.1% incidence rate of probable or confirmed IFI from a recent study that also looked at the use of VEN with either AZA or decitabine in patients with AML [ 9 ]. These consistent rates suggest a lower likelihood of IFI incidence than previously reported rates for newly diagnosed AML cohorts that were similarly treated, where the incidence of proven and possible IFIs was 16% for patients treated with hypomethylating agent–based induction therapy [ 12 ].…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies demonstrated that 84% of patients receiving VEN/AZA subsequently developed infections, compared to only 67% of patients in the control group [ 8 ]. In contrast, multiple studies have since shown that not only does use of VEN with a hypomethylating agent demonstrate incidence rates as low as 5.1% in proven and probable IFI for AML patients, but also that incidence rate does not significantly change with and without the use of antifungal prophylaxis [ 9 , 10 ]. This study evaluated the incidence of IFIs in AML patients treated with VEN/AZA to determine if antifungal prophylaxis is beneficial for this patient population.…”
mentioning
confidence: 99%
“…In spite of a profound neutropenia, MDS patients who are treated with hypomethylating agents rather than chemotherapy induction are not that prone to IA, indicating that the neutrophils rate probably does not account for the whole risk in AML patients [ 19 ]. Moreover, AML patients who are treated with the intermediate intensity scheme associating azacytidine and the apoptosis-restoring drug venetoclax seem to show intermediate risk of IMD, mostly IA, of between 5.1% and 19%, but data are still scarce on that point [ 20 ].…”
Section: Patientsmentioning
confidence: 99%
“…Hypomethylating agents and the anti-BCL2 inhibitor venetoclax are increasingly used for acute myeloid leukemias and myelodysplastic syndromes [ 76 , 77 ]. Similarly to BTKi, TKI and ruxolitinib, these agents are administered continuously, and may induce immune disruption with increased incidence of invasive fungal and bacterial infections [ 78 ]. Recently a seroconversion rate of about 90% was reported in AML/MDS patients vaccinated for SARS-CoV2 and treated with HMA alone or in combination with venetoclax ( Table 5 ) [ 79 , 80 ].…”
Section: Venetoclax and Hypometilating Agents (Hma)mentioning
confidence: 99%